Ockham and Chatton on Intellective Intuition - Amerini, Fabrizio (Vivarium, 2022)
Intellective intuitive cognition plays a key role in William of Ockham’s philosophy. On many occasions, Walter Chatton argues that this kind of cognition is unnecessary. Chatton has two main arguments for his point. First, he raises doubts about the possibility of distinguishing intellective intuitive cognition from sensory intuitive cognition. The former always arises with the latter, and whatever we can explain through the former, we can explain equally well through the latter. Second, he argues that we cannot separate the intellective intuitive cognition of a singular thing from the cognition of the species of that thing. We cannot intuitively and intellectively cognize a thing without recognizing that thing as a thing of a certain kind. Chatton’s conclusion is that since we can never experience an act of intellective intuitive cognition in itself, it is superfluous to posit this act of cognition. We can explain the singular cognition of an extramental singular simply by making the cognition of its species and the sensory intuitive cognition of it interact with each other.